2022
DOI: 10.3390/genes13101786
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and Experimental Analyses Reveal MAP4K4 as a Potential Marker for Gastric Cancer

Abstract: Background: Gastric cancer remains the most prevalent and highly lethal disease worldwide. MAP4K4, a member of Ste20, plays an important role in various pathologies, including cancer. However, its role in gastric cancer is not yet fully elucidated. Therefore, this study aims to determine the tumor-promoting role of MAP4K4 in gastric cancer and whether it can be used as a new and reliable biomarker to predict the prognosis of gastric cancer. For this purpose, we divide the samples into high- and low-expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Zhang et al reported overexpression of MAP4K4 kinase in gastric tumor samples. The overexpression of MAP4K4 was associated with gastric cancer’s invasion, progression, and metastasis, suggesting that MAP4K4 could serve as a prognostic marker for gastric cancer [ 77 ]. The regulatory role of MAP4K4 in GC cellular proliferation suggests that further in-depth study of MAP4K4 in GC is required to explore MAP4K4 as a therapeutic target.…”
Section: The Regulatory Functions Of Map4k4 In Malignant Diseasesmentioning
confidence: 99%
“…Zhang et al reported overexpression of MAP4K4 kinase in gastric tumor samples. The overexpression of MAP4K4 was associated with gastric cancer’s invasion, progression, and metastasis, suggesting that MAP4K4 could serve as a prognostic marker for gastric cancer [ 77 ]. The regulatory role of MAP4K4 in GC cellular proliferation suggests that further in-depth study of MAP4K4 in GC is required to explore MAP4K4 as a therapeutic target.…”
Section: The Regulatory Functions Of Map4k4 In Malignant Diseasesmentioning
confidence: 99%